Incidence and risk factors of active tuberculosis among older individuals with latent tuberculosis infection: a cohort study in two high-epidemic sites in eastern China - Zhu, Ping; Hao, Xiaogang; Wang, Wei; Wang, Wei; Xu, Bingjun; Zhan, Bingdong; Fang, Chunfu; Zhang, Yating; Gao, Yu; Chen, Bin (Frontiers in Cellular and Infection Microbiology, 2024)
Background The influencing factors of the process from latent tuberculosis infection (LTBI) to the onset of active tuberculosis (TB) remain unknown among different population groups, especially among older individuals in high-incidence areas. This study aimed to investigate the development of active TB among older adults with LTBI and identify groups in greatest need of improved prevention and control strategies for TB. Methods In 2021, we implemented an investigation among older individuals (≥ 65 years old) in two towns in Zhejiang Province with the highest incidence of TB. All participants underwent assessment using standardized questionnaires, physical examinations, interferon-gamma release assays, and chest radiography. All the participants with suspected TB based on the clinical symptoms or abnormal chest radiography results, as well as those with LTBI, were referred for diagnostic investigation in accordance with the national guidelines. Those with an initial diagnosis of TB were then excluded, whereas those with LTBI were included in a follow-up at baseline. Incident patients with active TB were identified from the Chinese Tuberculosis Management Information System, and a multivariate Cox regression model was used to estimate the incidence and risk of TB among those with LTBI. Results In total, 667 participants with LTBI were followed up for 1,315.3 person-years, revealing a disease density of 1,292.5 individuals/100,000 person-years (17/1,315.3). For those with LTBI, chest radiograph abnormalities had adjusted hazard ratios for active TB of 4.9 (1.6–15.3). Conclusions The presence of abnormal chest radiography findings increased the risk of active TB among older individuals with LTBI in high-epidemic sites in eastern China.